Experience of Using Letrozole as a First-Line Ovulation Induction Agent in Polycystic Ovary Syndrome (PCOS) - Nupur Nandi *, Mahua Bhattacharya, Amit Tolasaria and Banasree Bhadra (Al Ameen Medical College, 2011)
Objectives: To study the effects of aromatase inhibitor- letrozole, as a first-line ovulation inducing agent in anovulatory infertility due to PCOS (Polycystic ovary syndrome). Materials & Methods: This prospective study was conducted among 106 Women with PCOS (total 204 cycles). Letrozole was given as 2.5 mg. twice daily from day3 to day7 of menstrual cycle. Ultrasound folliculometry was started from day 8 onwards to monitor follicular development, ovulation & endometrial thickness. Timed intercourse was advised 24 hours after the leading follicular diameter reached >= 17 mm. in size till 12 hours post ovulation. Pregnancy detection was done by urine for pregnancy test once the menstruation was overdue & later confirmed by transvaginal sonography. Results: Out of 106 women, 72 women ovulated (67.9% ovulation rate), 29 women conceived (27.3% pregnancy rate), only 2 patients had miscarriage (1.8%). Over 204 cycles, per cycle pregnancy rate was 14.2%, & spontaneous ovulation rate was 35.2%. Average endometrial thickness on the day of documenting ovulation was 10.1 +- 0.3 mm. None had developed ovarian hyper stimulation syndrome or multiple gestations. Conclusion: This study indicates letrozole may safely be considered as an effective & simple first-line ovulation induction agent using minimal resources in anovulatory infertility due to PCOS.